Vaccination timeliness and associated factors among preterm infants at a tertiary hospital in Uganda - Nakatudde, Irene (PLoS One, 2019)
BACKGROUND: Preterm infants are at increased risk of infections including vaccine preventable diseases. Therefore, timely vaccination is crucial to ensure adequate disease protection. Information on whether preterm infants are vaccinated according to chronological age as recommended is limited in low-income countries. OBJECTIVES: We evaluated the timeliness of vaccination and associated factors among preterm infants at Mulago hospital, Uganda. METHODS: We conducted a mixed methods study between July 2016 and April 2017. Vaccination dates of preterm infants aged 6–24 months were obtained from child health cards. Additional data were collected using a questionnaire. Five key informant interviews with health workers and two focus group discussions with caregivers were conducted. Cox regression analysis was used to identify factors associated with vaccination timeliness. Qualitative data was transcribed and analysed manually using content thematic approach. RESULTS: We enrolled 350 preterm infants, with a median age of 8.4 months (IQR 6.8–10.8). Less than half, 149/350 (42.6%) of infants received all vaccines within the recommended time range. Timely vaccination was highest for BCG (92%) and lowest for OPV (45.4%). Untimely vaccination was highest for vaccines administered at 6 weeks (DPT 1, PCV 1 and OPV 1) compared to other vaccines in the EPI schedule. Delivering from home or private clinics and vaccine stock-out were significantly associated with untimely BCG and OPV 0 vaccination. Low maternal education level and being very preterm were associated with untimely DPT 1 and DPT 3 receipt. Admission and long stay in the neonatal unit were associated with untimely DPT 1 receipt while extreme low birth weight was associated with untimely DPT 3 vaccination. Increasing parity was associated with untimely measles vaccination. Qualitative findings revealed that lack of knowledge and poor attitudes of health workers and caregivers, gaps in documentation of vaccination status and inadequate communication by health workers hindered timely vaccination. CONCLUSION: More than half of preterm infants attending a specialised clinic at Mulago National Referral hospital in Uganda did not receive vaccines within the recommended time range. Specific strategies to improve vaccination timeliness in preterm infants are needed especially among the extremely low birth weight, very preterm and those with prolonged hospitalisation.